Numerical study of the influence of the Reynolds-number on the lift created by a leading edge vortex - Zhang, Xiaoqin. (2013)
We present a numerical study on the influence of the Reynolds-number on the lift enhancing effect of a leading edge vortex. Our approach is based on a combination of large-eddy simulations and the immersed boundary technique. We determine the influence of the leading edge vortex on the unsteady lift by simulating a fast pitch-up motion of the plate and studying the lift evolution after holding the flat plate fixed at an angle of attack. Our results suggest that an optimal Reynolds-number exists that maximizes the lift of the leading edge vortex, but that the lift-to-drag ratio is largely independent of the Reynolds-number above a Reynolds-number of Rec > 2000.